INCENTIVO À LEITURA: UMA REFLEXÃO A PARTIR DA ANÁLISE DE PROJETOS DO COLE - Faria, Thais (2006)
This work has the object to analise the resums of the notebooks in the three last COLEs (Reading Congress) - years 2001, 2003 and 2005-, looking for the incentives of reading projects, to recognize what is produced in our country about this theme. After this kno wleged, we intend to come back to Project Vô Di- Leitores de Luz made by me, looking for to analise your fundaments theorics medotology. By the way, the analises of the theorics projects and the objectives used, show what is produced in the Brazil and internalionality about reading, the incident of the formal education and informal education and the many of te projects that are for inicial grades, medial grade and gratuations, specializations and ONGs. One of the results of this job is the constation that happened a big incidence of projects in the formal education to the informal education, in the maiority of the incentive project are development by the ONGs in the COLEs.